(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Since ancient times India has been famous for its wisdom and itsthought. The ancient Persians, Greek and Romans were eager to learn from itssages and philosophers. When, in the eighteenth century, the first translationsof some Upanishads and the Bhagavad Gita became available to the West, Europeanphilosophers rhapsodized about the profundity and beauty of these writings.Here they encountered a fusion of philosophy and religion, a deep wisdom and aconcern with the ultimate that had no parallel in either contemporary Westernphilosophy or Western religion. Indian philosophy is highly sophisticated andvery technical and surpasses in both in volume and subtlety. In line with this,the paper focused about the analysis on ancient Indian sagacity and managementphilosophy.